2005
DOI: 10.1111/j.1365-2672.2004.02524.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of E. coli O157:H7 in organic wastes destined for land application

Abstract: Aim: To determine the persistence of Escherichia coli O157 in contrasting organic wastes spread to land and to assess the potential environmental risk associated with the disposal of these wastes to land. Methods and Results: Twenty-seven organic wastes originating from slaughterhouses, wastewater treatment plants (raw and treated sewage), creameries and farms (bovine slurry), were inoculated with E. coli O157:H7 and incubated at 10°C. Although pathogen numbers gradually declined in all the wastes, albeit at d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 26 publications
3
72
1
1
Order By: Relevance
“…Such water is obtained from shallow streams exposed to refuse-dumping and human/animal wastes. Other irrigation farms use untreated night soil as manure or organic fertilizer [17], wastes from abattoirs [18]. Sewage and surface run-offs [12] can contaminate fresh vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…Such water is obtained from shallow streams exposed to refuse-dumping and human/animal wastes. Other irrigation farms use untreated night soil as manure or organic fertilizer [17], wastes from abattoirs [18]. Sewage and surface run-offs [12] can contaminate fresh vegetables.…”
Section: Discussionmentioning
confidence: 99%
“…However, storage alone is not regarded as an effective way to inactivate pathogens in sludge (Carrington 1998). Avery et al (2005) monitored the decline in E. coli O157 in different wastes over 64 days. They concluded that the storage decreases the amount of E. coli O157 but does not eliminate the pathogen.…”
Section: Effect Of Storagementioning
confidence: 99%
“…Even if they can survive for many weeks on the soil after manure spreading, risk of water pollution by fecal microorganisms is highest soon after the spreading. On the other hand, some procedures can reduce the concentration of microorganisms in manure before spreading, such as aerobic or anaerobic digestion and composting [48,49].…”
Section: Agricultural Activitiesmentioning
confidence: 99%